2013
DOI: 10.1016/j.atherosclerosis.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polyvascular disease on clinical outcomes in patients undergoing coronary revascularization: An observation from the CREDO-Kyoto Registry Cohort-2

Abstract: Clinical outcome after coronary revascularization was worse in patients with prior stroke and/or EVD, which was mainly driven by the increased risk for non-coronary cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…These patients were not included in our PVD cohort, all of whom had PVD involving the aorta, renal arteries or extremities. There is some evidence that cerebrovascular disease may be a lesser risk factor for adverse outcomes after PCI than peripheral arterial disease 11,12 hence their inclusion in the PVD cohort may have reduced the apparent overall increased risk among their PVD group. The increased rate of adverse outcomes observed in our PVD group may be related to their higher rate of periprocedural bleeding events (3.8% vs. 2.4%, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…These patients were not included in our PVD cohort, all of whom had PVD involving the aorta, renal arteries or extremities. There is some evidence that cerebrovascular disease may be a lesser risk factor for adverse outcomes after PCI than peripheral arterial disease 11,12 hence their inclusion in the PVD cohort may have reduced the apparent overall increased risk among their PVD group. The increased rate of adverse outcomes observed in our PVD group may be related to their higher rate of periprocedural bleeding events (3.8% vs. 2.4%, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with subclinical ECADs were more often on ASA, beta blockers, ACE-I/ARB, and statins at admission than those without ECAD. However, medication at admission was not accounted for in most previous studies [4,5,7,12,16,25]. Participants with clinical ECAD had higher frequency of statin treatment at admission.…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies have shown that patients with CAD and concomitant clinical ECADs are at increased risk of recurrent adverse cardiovascular events and mortality [4,5,7,9,10,18]. The frequency of ECAD among patients with AMI is substantial and vary between 13 and 43%, depending on study population and definition of ECAD [4,7,8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, triple-vessel and left main coronary artery disease and peripheral artery disease were most frequently found in the ECAS + ICAS group. Polyvascular disease and high systemic atherosclerosis burden were previously shown to be associated with increased risk of adverse cardiovascular outcomes [24][25][26].…”
Section: Discussionmentioning
confidence: 99%